Review of models that integrate Design Thinking in Agile Development methodologies - Chavez Ponce , Dewitt Scott (2022)
The article exposed aims to make a review of Design Thinking (DT)Integration in software development, using the SCRUM  methodology. It tries adding Scrum techniques to DT class based on projects. The main objective is to provide useful project management that fit well with the rest of the DT tools kit. As a result, it is observed that Scrum during the start of the projects, together with a lot of other new information, did not give participants enough time to assimilate everything completely, although the students seemed to like the use of scrum and its techniques